THE INFLUENCE OF THE PRE-MARITAL CLASS-BASED SOCIAL MEDIA ON THE READINESS OF REPRODUCTIVE HEALTH IN THE FACE OF THE WEDDING ON THE BRIDE AND GROOMm - Ni Nyoman Sasnitiari; Risna Dewi Yanti (Poltekkes Kemenkes Bandung, 2020)
The low participation of the bride and groom follow the course of a prenuptial is a serious issue and requires appropriate solutions. One of the efforts to provide health information to the prospective brides, namely by forming a pre-marital class-based social media. The bride and groom who do not follow a course of pre-marital collected in One group social media and given the knowledge according to the syllabus of a course of pre-marital. This research aimed to determine the influence of the Pre-Marital Class on the readiness of reproductive health for marriage.This research is quantitive research with the quasi-experimental design of this research using the randomized pre and post-test with control group design. The place of the study was in the Bogor city start in July until October 2018 with the sample of the girl bride and groom several 42 persons in each group with a total of sample 84 persons. Data collection was conducted using a questionnaire of readiness.Research results there is no difference in the mean of the readiness of reproductive health in the face of pre-marital between the intervention group with a control group with a p-value of 0.057 (p<0.05). If seen from the median increase in readiness, then the control group had improved better than the intervention group.The conclusion is there is no difference between the intervention group using pre-marital group social media by WhatsApp with the group courses pre-marital that held by the ministry of the religious affair at Bogor city.